Assessment of food insecurity and nutritional outcomes in Bachok, Kelantan - Ali Naser, Ihab; A. J., Rohana; Wan Muda, Wan Manan; Wan Nik, Wan Suriati; Mohd Shariff, Zalilah; A., Mohamad Rusli (OMICS International, 2015)
Aim: This study is to examine the association between food insecurity and nutritional outcomes among children and adults and its impact on the quality of life of the mother in rural sample in Bachok-Kelantan. Method: A cross-sectional survey of low income households was conducted and 223 households of mothers aged 18-55 years old, non-lactating, non-pregnant mother and having at least one child in 2-12 years range were purposively selected. A questionnaire was administered including the Radimer/Cornell scale; items on sociodemographic characteristics, anthropometric measurements and quality of life tool (SF36). Results: The study reported that 16.1% of the households were food secure, while 83.9% experienced some kind of food insecurity, (29.6% households were food insecure, 19.3% individuals were food insecure and 35.0% fell into the child hunger category). The prevalence of underweight, stunting and wasting among the food insecure children were 61.0%, 61.4% and 30.6% respectively, and the prevalence of weight-for-height (overweight) was 1.3%. Based on multinomial logistic regression, larger household size (OR=1.776; 95%C.I, 1.35, 2.32; p<0.001), number of children in the household ( OR=1.20; 95%CI,1.025, 1.42; p=0.024), total monthly income (OR=0.977; 95% CI, 0.995, 0.998; p<0.001), income per capita (OR=0.98; 95% CI, 0.97, 0.98; p<0.001) and food expenditure (OR=0.977; 95% CI, 0.99, 1.00; p=0.049) were found to be significant risk factors for household food insecurity. This study showed there was an association between food insecurity and Diet Dietary score and dietary pattern. Furthermore, food insecure households had lower intake of animal protein, fruits and vegetables compared to their counterparts in the food secure group. The findings of the study reveal that the children in the food insecure were 2.15 times more likely to be underweight and 3 times more likely to be stunted than the children in the food secure households, while no association with wasting was reported. Although, the study reported higher prevalence of overweight and obese mothers (52%) and (47.1%) at-risk WC (≥80 cm), no significant association has been found between food insecurity, BMI and waist circumferences. The score for all the eight domains of quality of life were negatively associated with food insecurity. Conclusion: Our study showed that food insecurity in low income households from Bachok´ is highly prevalent and associated with poor living conditions and it highlighted the pervasive vulnerability of individuals living in food insecure households. In addition to nutritional problems, food insecure households in Bachok- Kelantan struggle with a broad spectrum of health- related problems.